Weak Tradeoff and Strong Segmentation Among Plant Hydraulic Traits During Seasonal Variation in Four Woody Species - Liu, Xiao; Li, Qiang; Wang, Feng; Sun, Xiaohan; Wang, Ning; Song, Huijia; Cui, Rong; Wu, Pan; Du, Ning; Wang, Hui; Wang, Renqing (Frontiers in Plant Science, 2020)
Plants may maintain long-term xylem function via efficiency-safety tradeoff and segmentation. Most studies focus on the growing season and community level. We studied species with different efficiency-safety tradeoff strategies, Quercus acutissima, Robinia pseudoacacia, Vitex negundo var. heterophylla, and Rhus typhina, to determine the seasonality of this mechanism. We separated their branches into perennial shoots and terminal twigs and monitored their midday water potential (Ψmd), relative water content (RWC), stem-specific hydraulic conductivity (Ks), loss of 12, 50, and 88% of maximum efficiency (i.e., P12, P50, P88) for 2 years. There were no correlations between water relations (Ψmd, RWC, Ks) and embolism resistance traits (P12, P50, P88) but they significantly differed between the perennial shoots and terminal twigs. All species had weak annual hydraulic efficiency-safety tradeoff but strong segmentation between the perennial shoots and the terminal twigs. R. pseudoacacia used a high-efficiency, low-safety strategy, whereas R. typhina used a high-safety, low-efficiency strategy. Q. acutissima and V. negundo var. heterophylla alternated these strategies. This mechanism provides a potential basis for habitat partitioning and niche divergence in the changing warm temperate zone environment.